Ultrasound Morphologic Features of Steatocystoma Multiplex With Clinical Correlation. (1st May 2020) - Arceu, Montserrat; Martinez, Guisella; Alfaro, Daniela; Wortsman, Ximena
Abstract : The ultrasound features of 87 steatocytoma multiplex (SCM) lesions detected in 9 patients are reported. Steatocytoma multiplex is a hamartomatous condition derived from the pilosebaceous duct junction that generates multiple cutaneous cystic lesions. It appeared as clusters of well‐defined hypoechoic nodules with mild posterior enhancement in 100% of cases, with both dermal and subcutaneous locations in 67%. No calcification foci were detected within or at the periphery of the lesions. Fifty‐six percent of the cases showed signs of hypervascularity in the edge of the nodules, and 44% of the lesions were associated with another dermatologic condition, most frequent being hidradenitis suppurativa (75%), followed by vellus hair cysts (25%). Steatocytoma multiplex shows ultrasound features that allow discrimination from other common cutaneous entities.